Kontribusi Dukungan Orangtua dan Persepsi Siswa tentang Disiplin Belajar terhadap Perilaku Membolos serta Implikasinya terhadap Layanan Bimbingan dan Konseling - Khadijah, Khairiyah; Marjohan, Marjohan; Bentri, Alwen (Universitas Negeri Padang, 2016)
Truancy is an action of missing full day school or skipping certain classes during school hours. It is considered as a non-adaptive behaviour that needs serious attention. Truancy is affected by several factors. Some of the factors are (1) family in which parents give lack of support to their children in learning and, (2) individual involving the students’ perception on learning discipline. This research is intended to describe: (1) the parents’ support, (2) the students’ perception toward learning discipline, (3) truancy behaviour, and to test, (4) the contribution of the parents’ support toward truancy behaviour, (5) the contribution of the students’ perception on learning discipline toward truancy behaviour, and (6) the contribution of the parents’ support and the students’ perception on learning discipline simultaneously toward truancy behaviour. This research applied quantitative method and descriptive correlational design. The population of the research was 533 students in class X and XI of SMAN 8 Padang. Of the population, 229 were taken as the sample. They were chosen by using Proportional Stratified Random Sampling technique. The instrument of the research was a scale of Likert model. The data were analyzed by using descriptive statistic, simple regression and multiple regression. The research findings show that: (1) on average, the parents’ support is in high category, (2) the students’ perception on learning discipline is in positive category, (3) the truancy behaviour is in average category, (4) the parents’ support contributed 6,2% (R= 0.249 on significance level 0.000) toward truancy behaviour, (5) the students’ perception on learning discipline contributed 10.9% (R= 0.331 on significance level 0.000) toward truancy behaviour, and (6) simultaneously, the parents’ support and the students’ perception on learning discipline contributed 12.7% (R= 0.356 on significance level 0.000) toward truancy behaviour. The implication of the research findings is expected to be used as an analysis on the students’ need in designing Guidance and Counselling program at SMAN 8 Padang.